Diseño conceptual de un bio-recubrimiento a base de almidón de yuca modificado con aceite esencial de tomillo como principio activo para el control de Colletotrichum gloeosporioides aislado de aguacate hass colombiano (2020)
Bio coatings are pre-formed films or applied directly on fruit and vegetable products in order to extend their useful life. Currently, they are also used as matrices for antifungal active principles that control the incidence of some infectious diseases such as Stem-End Rot or anthracnose. In the present work the conceptual design of a bio-coating whose matrix is based on cassava starch modified with acetic acid, and thyme essential oil as an antifungal principle is carried out. In order to propose a coating that reduces the incidence of the Colletotrichum gloeosporioides fungus in the Colombian Persea americana mill avocado. For this purpose, the methodology for the in vitro analysis of the essential oil on the fungus, the formulation of the film-forming solution and the methodology for the in vitro and in situ evaluation of the same is proposed.--Taken from the Degree Document Format.